3D Photonic Nanostructures via Diffusion-Assisted Direct fs Laser Writing. (4th September 2012) - Bickauskaite, Gabija; Manousidaki, Maria; Terzaki, Konstantina; Kambouraki, Elmina; Sakellari, Ioanna; Vasilantonakis, Nikos; Gray, David; Soukoulis, Costas M.; Fotakis, Costas; Vamvakaki, Maria; Kafesaki, Maria; Farsari, Maria; et al.
Abstract : We present our research into the fabrication of fully three-dimensional metallic nanostructures using diffusion-assisted direct laser writing, a technique which employs quencher diffusion to fabricate structures with resolution beyond the diffraction limit. We have made dielectric 3D nanostructures by multiphoton polymerization using a metal-binding organic-inorganic hybrid material, and we covered them with silver using selective electroless plating. We have used this method to make spirals and woodpiles with 600 nm intralayer periodicity. The resulting photonic nanostructures have a smooth metallic surface and exhibit well-defined diffraction spectra, indicating good fabrication quality and internal periodicity. In addition, we have made dielectric woodpile structures decorated with gold nanoparticles. Our results show that diffusion-assisted direct laser writing and selective electroless plating can be combined to form a viable route for the fabrication of 3D dielectric and metallic photonic nanostructures.